2005
DOI: 10.1007/s10620-005-2810-7
|View full text |Cite
|
Sign up to set email alerts
|

Rebamipide Significantly Inhibits Indomethacin-Induced Mitochondrial Damage, Lipid Peroxidation, and Apoptosis in Gastric Epithelial RGM-1 Cells

Abstract: Nonsteroidal antiinflammatory drugs (NSAIDs) cause complications such as gastrointestinal injury. NSAIDs were recently reported to cause mitochondrial injury: to dissipate the mitochondrial transmembrane potential (MTP), and to induce mitochondrial permeability transition pore (PTP), which liberates cytochrome c. This enzyme generates reactive oxygen species (ROS) thereby triggers caspase cascade and cellular lipid peroxidation, resulting in cellular apoptosis. However, the mechanism of this NSAID-induced MTP'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 24 publications
5
60
1
4
Order By: Relevance
“…Furthermore, in vitro studies using intestinal epithelial cell lines also have indicated that indomethacin induced apoptosis of the intestinal epithelial cells accompanied by an increased production of reactive oxygen species (ROS) (26,27). Omatsu et al (28) have reported that indomethacin induced small intestinal epithelial apoptosis through ROS production and subsequent release of cytochrome c and smac/DIABLO and the activation of caspase-3 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in vitro studies using intestinal epithelial cell lines also have indicated that indomethacin induced apoptosis of the intestinal epithelial cells accompanied by an increased production of reactive oxygen species (ROS) (26,27). Omatsu et al (28) have reported that indomethacin induced small intestinal epithelial apoptosis through ROS production and subsequent release of cytochrome c and smac/DIABLO and the activation of caspase-3 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Hoechst 33258 was used for examination of chromatin DNA. We observed the fluorescent nuclei showing apoptotic changes, mainly due to chromatin condensation at 200 × and 1,000 × magnification [17]. Further, at 18, 24, 30 hr after inoculation, we counted 10 microscopic fields at 400 × magnification the number fluorescent cells infected with M. hyorhinis showing apoptotic changes, AsA+ or AsA-.…”
Section: Cell Culturesmentioning
confidence: 99%
“…Mitochondrial activity was examined by microscopic observation of the AZ-521 cells stained with MitoRed [17]. Hoechst 33258 was used for examination of chromatin DNA.…”
Section: Cell Culturesmentioning
confidence: 99%
“…NSAIDs cause mitochondrial injury by dissipating the mitochondrial transmembrane potential and inducing mitochondrial permeability transition pore, which liberates cytochrome C. This enzyme generates reactive oxygen species which trigger the cellular lipid peroxidation, resulting in cellular apoptosis 17 . Earlier findings have also suggested that NSAIDs raise the MDA level with respect to the control value representing their significant lipid peroxidation activity 18 .…”
Section: S Of Anterior Latissimus Dorsi Muscle Of Diclofenac Treatedmentioning
confidence: 99%